Exogenous abscisic acid prolongs the dormancy of recalcitrant seed of Panax notoginseng - Wang, Qing-Yan; Yang, Ling; Ge, Na; Jia, Jin-Shan; Huang, Rong-Mei; Chen, Cui; Meng, Zhen-Gui; Li, Long-Gen; Chen, Jun-Wen (Frontiers in Plant Science, 2023)
The seeds of Panax notoginseng (Burk.) F. H. Chen, are typically characterized by their recalcitrance and after-ripening process, and exhibit a high water content at harvest as well as a high susceptibility to dehydration. The storage difficulty and the low germination of recalcitrant seeds of P. notoginseng are known to cause an obstacle in agricultural production. In this study, the ratio of embryo to endosperm (Em/En) in abscisic acid (ABA) treatments (1 mg·L-1 & 10 mg·L-1, LA & HA) were 53.64% and 52.34%, respectively, which were lower than those in control check (CK) (61.98%) at 30 days of after-ripening process (DAR). A total of 83.67% of seeds germinated in the CK, 49% of seeds germinated in the LA treatment, and 37.33% of seeds germinated in the HA treatment at 60 DAR. The ABA, gibberellin (GA) and auxin (IAA) levels were increased in the HA treatment at 0 DAR, while the jasmonic acid (JA) levels were decreased. The ABA, IAA and JA were increased, but GA was decreased with HA treatment at 30 DAR. A total of 4,742, 16,531 and 890 differentially expressed genes (DEGs) were identified between the HA-treated and CK groups, respectively, along with an obvious enrichment in ABA-regulated plant hormone pathway and mitogen-activated protein kinase (MAPK) signaling pathway. The expression of pyracbactin resistance-like (PYL) and SNF1-related protein kinase subfamily 2 (SnRK2s) increased in the ABA-treated groups, whereas the expression of type 2C protein phosphatase (PP2C) decreased, those of which are related to ABA signaling pathway. As a result of the changes in expression of these genes, the increased ABA signaling and suppressed GA signaling could inhibit the growth of embryo and the expansion of developmental space. Futhermore, our results demonstrated that MAPK signaling cascades might be involved in the amplification of hormone signaling. Meanwhile, our study uncovered that exogenous hormone ABA could inhibit the embryo development, promote dormancy, and delay germination in recalcitrant seeds. These findings reveal the critical roles of ABA in regulating the dormancy of recalcitrant seeds, and therby provide a new insight for recalcitrant seeds in agricultural production and storage.